Evaluación de las Propiedades Reológicas y Térmicas de un Asfalto Convencional y Uno Modificado con un Desecho de PEBD - Castro López, William Andrés; Rondón Quintana, Hugo Alexander; Barrero Calixto, Juan Carlos (Ingeniería, 2016)
Context: The asphalt technology and modified asphalt mixtures has been widely used and studied, worldwide. Adding polymers to asphalt modifies mechanical, chemical and rheological properties, trying to improve behavior of the mixtures subjected to different environmental and load conditions. The paper report results from rheological and thermal characterization on conventional 60-70 asphalt cement and 60-70 asphalt cement modified by introducing a waste of low density polyethylene (LDPE). Method: Modification of the asphalt was performed by wet way in a proportion of LDPE/CA=5% with respect to the mass. Rheological (using DSR), Thermogravimetry (TGA) and Differential Scanning Calorimetry (DSC) techniques were performed. Results and Conclusions: The modified asphalt develops a remarkable increase in stiffness and improvement of the performance grade at high temperatures of service. Additionally, the modified asphalt is more resistant to oxidation and aging processes due to heat. However, the asphalt modified showed a decrease in crack resistance at low and intermediate temperatures of service.